Metals for joint replacement - Konttinen, Y; Milošev, Ingrid; Trebše, Rihard; Rantanen, P; Tiainen, Veli Matti; Virtanen, Sannakaisa; et al. (Joint Replacement Technology, 2008)
This chapter provides first three different classifications of biomaterials in general, based on their composition, surface reactivity and production, which will help to put metals in context with everyday life. Not all metals can be used as biomaterials since their use in the human body is tightly regulated; the general principles and specific EU standards well reflect the global status and trends in the regulatory field. Metal ions are held together by metallic bonds, which consist of relatively loosely bound valence electrons. The positive metal ions are located in crystal lattice points, which are surrounded by electrons. This provides metals with special properties, such as good thermal and electrical conductivity, metallic lustre, but also their ductile and malleable properties; that is, the ability to undergo plastic deformation without breaking. Most of the technically important metallic materials are thermodynamically not stable in the metallic state in air or in aqueous solutions. Instead, surface oxidation would take place, during which the metal loses electrons. The oxidized metal ions would either dissolve (corrosion) or form an oxide film on the metal surface (passivity). The chapter provides an overview of the surgical use of steel, titanium, cobalt-based alloys and tantalum. Some future trends such as mini-invasive surgery, resurfacing implants, isoelastic implants, implant coating and osseo-integrating implants have been discusse